Polypropylene Composites

The polypropylene composite material addresses the limitations of existing materials by incorporating an olefinic polymer that enhances mechanical and impact strength through improved crystallinity and miscibility, resulting in a material with superior rigidity and resistance.

JP7662266B2Active Publication Date: 2025-04-15LG CHEM LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023183193
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2023-10-25
Publication Date
2025-04-15
Estimated Expiration
2040-09-28

AI Technical Summary

Technical Problem

Existing polypropylene composite materials face limitations in ensuring impact resistance across various usage environments, necessitating the development of materials with enhanced mechanical strength and impact strength properties.

Method used

A polypropylene composite material is formulated by incorporating an olefinic polymer that meets specific criteria, including a melt index range of 0.1g/10 min to 10.0g/10 min, a density of 0.860g/cc to 0.880g/cc, and specific melting temperature fractions, which allows for excellent miscibility with polypropylene and uniform dispersion within the composite.

Benefits of technology

The resulting polypropylene composite exhibits high mechanical rigidity due to the introduction of a highly crystalline region, leading to improved mechanical strength and significantly enhanced impact strength properties without the need for additional additives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662266000013
    Figure 0007662266000013
  • Figure 0007662266000014
    Figure 0007662266000014
  • Figure 0007662266000015
    Figure 0007662266000015
Patent Text Reader

Abstract

To provide a polypropylene-based composite material which can exhibit remarkably improved impact strength characteristics in addition to excellent mechanical strength.SOLUTION: A polypropylene-based composite material, which contains (A) polypropylene and (B) an olefinic polymer satisfying requirements of (1) a melting index (Melt Index, MI, and loading conditions of 190°C and 2.16 kg) of 0.1 g / 10 min to 10.0 g / 10 min, (2) a melting temperature of 20°C to 70°C, at the time of measurement by a differential scan calorimeter (DSC), and (3) a high temperature melting peak confirmed at 75°C to 150°C at the time of measurement by a differential scan calorimeter precise measurement method (SSA), and a total H (75) of a heat capacity of the region of 1.0 J / g or more, can exhibit excellent impact strength.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2019-0121150, filed on September 30, 2019, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a polypropylene-based composite material, and more particularly to a polypropylene-based composite material having improved impact strength and mechanical properties by containing a low-density olefin-based polymer having high mechanical rigidity due to the introduction of highly crystalline regions. [Background technology]

[0003] Generally, polypropylene-based resin compositions containing polypropylene (PP) as a main component and containing an impact reinforcing material and an inorganic filler have been used as compositions for interior and exterior material parts of automobiles.

[0004] Until the mid-1990s, before the development of ethylene-α-olefin copolymers polymerized using metallocene catalysts, EPR (ethylene propylene rubber) and EPDM (ethylene propylene diene rubber) were mainly used as impact reinforcement materials in polypropylene resin compositions for automobile interior and exterior materials, especially bumper covers. However, after the appearance of ethylene-α-olefin copolymers synthesized using metallocene catalysts, ethylene-α-olefin copolymers began to be used as impact reinforcement materials, and are now the mainstream. The reason for this is that polypropylene composite materials using these have many advantages, such as well-balanced physical properties such as impact strength, elastic modulus, and flexural strength, excellent moldability, and low cost.

[0005] Polyolefins such as ethylene-α-olefin copolymers synthesized by metallocene catalysts have a narrower molecular weight distribution and better mechanical properties than those synthesized by Ziegler-Natta catalysts because the molecular structure is more uniformly controlled. Low-density ethylene elastomers polymerized by metallocene catalysts also have the characteristic that the α-olefin copolymer monomer is inserted relatively uniformly into the polyethylene (PE) molecule compared to those synthesized by Ziegler-Natta catalysts, so they maintain low-density rubber properties and also have other good mechanical properties.

[0006] However, there is a limit to how much impact resistance can be ensured depending on the various usage environments, and there is a demand for the development of polypropylene-based composite materials that can overcome such limitations. Summary of the Invention [Problem to be solved by the invention]

[0007] The problem to be solved by the present invention is to provide a polypropylene-based composite material which can exhibit significantly improved impact strength properties together with excellent mechanical strength. [Means for solving the problem]

[0008] In order to solve the above problems, the present invention provides a polypropylene composite material comprising (A) a polypropylene and (B) an olefin polymer satisfying the following requirements (1) to (3):

[0009] (1) the melt index (MI, 190°C, 2.16 kg load condition) is 0.1 g / 10 min to 10.0 g / 10 min, (2) the density (d) is 0.860 g / cc to 0.880 g / cc, (3) when measured by differential scanning calorimetry (SSA), T(90)-T(50)≦50 and T(95)-T(90)≧10, Here, T(50), T(90) and T(95) are the temperatures at which 50%, 90% and 95% melt, respectively, when the temperature-heat capacity curve is fractionated in the measurement results by the differential scanning calorimeter precision measurement method (SSA). Effect of the Invention

[0010] The polypropylene-based composite material according to the present invention contains an olefin-based polymer that exhibits high mechanical rigidity due to the introduction of highly crystalline regions and can be uniformly dispersed within the composite material due to its excellent miscibility with polypropylene, and therefore can exhibit excellent mechanical strength as well as significantly improved impact strength properties without the use of any other additives. [Brief description of the drawings]

[0011] [Figure 1] 1 is a graph showing the results of measuring the melting temperature of the polymer of Example Production Example 1 using a differential scanning calorimeter (DSC). [Diagram 2] 1 is a graph showing the results of measuring the melting temperature of the polymer of Comparative Production Example 1 using a differential scanning calorimeter (DSC). [Diagram 3] 1 is a graph showing the results of measurement of the polymer of Example Production Example 1 by a differential scanning calorimeter precision measurement method (SSA). [Figure 4] 1 is a graph showing the results of measurement of the polymer of Comparative Production Example 1 by a differential scanning calorimeter precision measurement method (SSA). [Diagram 5] 1 is a graph showing T(50), T(90), and T(95) obtained by fractionating the results of measurement of the polymer of Example 1 by a differential scanning calorimeter precision measurement method (SSA). [Figure 6] 1 is a graph showing T(50), T(90), and T(95) obtained by fractionating the results of measurement of the polymer of Comparative Production Example 1 by a differential scanning calorimeter precision measurement method (SSA). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In the following, the present invention will be described in more detail in order to facilitate understanding of the present invention.

[0013] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0014] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerization of the same or different types of monomers. The generic term "polymer" includes the terms "homopolymer," "copolymer," "terpolymer," and "hybrid polymer." The term "hybrid polymer" also refers to a polymer prepared by polymerization of two or more different types of monomers. The generic term "hybrid polymer" includes the term "copolymer" (usually used to refer to a polymer prepared from two different types of monomers) as well as the term "terpolymer" (usually used to refer to a polymer prepared from three different types of monomers). This includes polymers prepared by polymerization of four or more types of monomers.

[0015] Polypropylene is generally used as an interior and exterior material for automobiles such as automobile bumpers, and polyolefin polymers are used together as impact reinforcement materials to complement the low impact strength of polypropylene. Among them, low-density polyolefin polymers are used in order to exhibit properties such as impact resistance, elastic modulus, and tensile properties under various usage environments and to have high impact strength properties, but in this case, there is a problem that the strength of polypropylene is rather reduced.

[0016] In contrast, in the present invention, an olefin polymer is used in the production of a polypropylene composite material, which exhibits an excellent effect of improving impact strength and can be uniformly dispersed in the composite material due to its excellent miscibility with polypropylene, thereby making it possible to exhibit remarkably improved impact strength properties together with excellent mechanical strength without using any other additives.

[0017] The polypropylene composite material according to the present invention contains (A) polypropylene and (B) an olefin polymer that satisfies the following requirements (1) to (3).

[0018] (1) The melt index (MI, 190°C, 2.16 kg load) is 0.1 g / 10 min to 10.0 g / 10 min, (2) the density (d) is 0.860 g / cc to 0.880 g / cc, and (3) when measured by differential scanning calorimetry (SSA), T(90)-T(50)≦50 and T(95)-T(90)≧10.

[0019] Here, T(50), T(90) and T(95) are the temperatures at which 50%, 90% and 95% melt, respectively, when the temperature-heat capacity curve is fractionated as measured by the differential scanning calorimeter (SSA).

[0020] Each component will be described in detail below.

[0021] (A) Polypropylene In the polypropylene-based composite according to an embodiment of the present invention, the polypropylene may be, specifically, a polypropylene homopolymer or a copolymer of propylene and an alpha-olefin monomer, and the copolymer may be an alternating, random, or block copolymer. However, in the present invention, the polypropylene is a compound different from the olefin polymer, excluding those that may overlap with the olefin polymer.

[0022] Specifically, the alpha-olefin monomer may be an aliphatic olefin having 2 to 12 carbon atoms or 2 to 8 carbon atoms. More specifically, ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-icosene, 4,4-dimethyl-1-pentene, 4,4-diethyl-1-hexene, or 3,4-dimethyl-1-hexene may be used alone or in combination.

[0023] More specifically, the polypropylene may be any one or a mixture of two or more selected from the group consisting of polypropylene copolymers, propylene-alpha-olefin copolymers, and propylene-ethylene-alpha-olefin copolymers, and in this case, the copolymers may be random or block copolymers.

[0024] The polypropylene has a melt index (MI) of 0.5 g / 10 min to 100 g / 10 min measured at 230° C. under a load of 2.16 kg, specifically, the melt index (MI) may be 1 g / 10 min to 90 g / 10 min, more specifically, 10 g / 10 min to 50 g / 10 min. If the melt index of the polypropylene is out of the above range, problems may occur during injection molding.

[0025] Specifically, in the polypropylene-based composite according to an embodiment of the present invention, the polypropylene may be an impact copolymer having a melt index (MI) of 0.5 g / 10 min to 100 g / 10 min, specifically 1 g / 10 min to 90 g / 10 min, measured at 230° C. under a load of 2.16 kg, more specifically propylene-ethylene impact copolymer, and the impact copolymer may be included in an amount of 50 wt % to 90 wt %, more specifically 80 wt % to 90 wt %, based on the total weight of the polypropylene-based composite. When the impact copolymer having such physical properties is included as polypropylene in the above content range, strength properties, particularly low-temperature strength properties, can be improved.

[0026] The impact copolymer can be produced by a conventional polymer production reaction so as to satisfy the above physical property requirements, or can be obtained commercially and used. TM Examples include the M1600.

[0027] In addition, in the polypropylene-based composite according to an embodiment of the present invention, the polypropylene may be one or more random propylene copolymers having a DSC melting point in the range of 120°C to 160°C and a melt flow rate (MFR) in the range of 5g / 10min to 120g / 10min measured at 230°C and a load of 2.16kg according to ASTM-D1238, and the random propylene copolymer may be contained in an amount of 75% by weight to 97% by weight, more specifically, 85% by weight to 91% by weight, based on the total weight of the polypropylene-based composite. When the polypropylene having such physical properties is contained in the above content range, the mechanical strength of the polypropylene composite, such as hardness, can be improved. The random propylene copolymer may be produced to satisfy the above physical property requirements using a conventional polymer production reaction, or may be commercially available for use. As a specific example, Braskem America Inc.'s BraskemTM PP R7021-50RNA or Formolene from Formosa Plastics Corporation of the United States TM Examples include 7320A.

[0028] (B) Olefin polymer The olefin polymer contained in the polypropylene composite material according to the present invention has an ultra-low density, and when compared with conventional olefin polymers, a high crystalline region is introduced to exhibit higher tensile strength and tear strength when the polymer has the same level of density and melt index (Melt Index, MI, 190°C, 2.16 kg load condition). The olefin polymer contained in the polypropylene composite material according to the present invention is produced by a production method including a step of polymerizing an olefin monomer while introducing hydrogen gas in the presence of a polymerization catalyst composition, and during polymerization, a high crystalline region is introduced by the introduction of hydrogen gas, exhibiting excellent mechanical rigidity.

[0029] The melt index (MI) can be adjusted by adjusting the amount of catalyst used in the polymerization process of the olefin polymer relative to the amount of comonomer, and affects the mechanical properties, impact strength, and moldability of the olefin polymer. In this specification, the melt index is measured under low density conditions of 0.850g / cc to 0.890g / cc, 190°C, and a load of 2.16kg according to ASTM D1238, and may be 0.1g / 10min to 10g / 10min, specifically 0.3g / 10min to 9g / 10min, and more specifically 0.4g / 10min to 7g / 10min.

[0030] On the other hand, the density is 0.850 g / cc to 0.890 g / cc, specifically, may be 0.850 g / cc to 0.880 g / cc, and more specifically, may be 0.860 g / cc to 0.875 g / cc.

[0031] Generally, the density of an olefin polymer is affected by the type and content of the monomer used during polymerization, the degree of polymerization, etc., and in the case of a copolymer, it is greatly affected by the content of the comonomer. The olefin polymer of the present invention is polymerized using a catalyst composition containing a transition metal compound having a characteristic structure, and it is possible to introduce a large amount of comonomer, so that the olefin polymer of the present invention can have a low density within the above-mentioned range.

[0032] In addition, the olefin polymer may have a property, as measured by a differential scanning calorimeter (SSA), that is, T(90)-T(50)≦50, T(95)-T(90)≧10, specifically, 20≦T(90)-T(50)≦45, 10≦T(95)-T(90)≦30, and more specifically, 30≦T(90)-T(50)≦40, 10≦T(95)-T(90)≦20.

[0033] The T(50), T(90) and T(95) are the temperatures at which 50%, 90% and 95% of the material melts, respectively, when the temperature-heat capacity curve is fractionated as measured by the differential scanning calorimeter (SSA).

[0034] In general, the measurement of the melting temperature (Tm) using a differential scanning calorimeter (DSC) involves a first cycle of heating at a constant rate to a temperature about 30°C higher than the melting temperature (Tm) and then cooling at a constant rate to a temperature about 30°C lower than the glass transition temperature (Tg), followed by a second cycle to obtain a standard melting temperature (Tm) peak. The measurement using the differential scanning calorimeter precision measurement method (SSA) is a method of obtaining more precise crystal information by repeatedly performing a process of heating and cooling to a temperature just before the melting temperature (Tm) peak after the first cycle using a differential scanning calorimeter (DSC), followed by heating and cooling to a temperature about 5°C lower, followed by cooling (Eur.Polym.J.2015,65,132).

[0035] When a small amount of highly crystalline regions is introduced into an olefin polymer, the melting temperature is not measured using a general differential scanning calorimeter (DSC), but a high-temperature melting peak can be measured using the above-mentioned differential scanning calorimeter precision measurement method (SSA).

[0036] The olefin polymer according to one embodiment of the present invention may further satisfy the requirement (4) that the weight average molecular weight (Mw) is 10,000 g / mol to 500,000 g / mol, and specifically, the weight average molecular weight (Mw) may be 30,000 g / mol to 300,000 g / mol, more specifically, 50,000 g / mol to 200,000 g / mol. In the present invention, the weight average molecular weight (Mw) is a polystyrene-equivalent molecular weight analyzed by gel permeation chromatography (GPC).

[0037] In addition, the olefin polymer according to one embodiment of the present invention may further satisfy the requirement that (5) the molecular weight distribution (MWD), which is the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn), is 0.1 to 6.0. Specifically, the molecular weight distribution (MWD) may be 1.0 to 4.0, more specifically, 2.0 to 3.0.

[0038] Furthermore, the olefin polymer according to one embodiment of the present invention can further satisfy the requirement (6) that the melting point (Tm) is 20°C to 70°C when measured by a differential scanning calorimeter (DSC), and the melting point (Tm) may be specifically 25°C to 60°C, and more specifically 25°C to 50°C.

[0039] The olefin polymer may be a homopolymer of an olefin monomer, specifically, any one selected from an alpha-olefin monomer, a cyclic olefin monomer, a diene olefin monomer, a triene olefin monomer, and a styrene monomer, or a copolymer of two or more of them. More specifically, the olefin polymer may be a copolymer of ethylene and an alpha-olefin having 3 to 12 carbon atoms, or a copolymer of an alpha-olefin having 3 to 10 carbon atoms.

[0040] The alpha-olefin comonomer may include any one or a mixture of two or more selected from the group consisting of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-icosene, norbornene, norbornadiene, ethylidene norbornene, phenylnorbornene, vinylnorbornene, dicyclopentadiene, 1,4-butadiene, 1,5-pentadiene, 1,6-hexadiene, styrene, alpha-methylstyrene, divinylbenzene, and 3-chloromethylstyrene.

[0041] More specifically, the olefin copolymer according to one embodiment of the present invention may be a copolymer of ethylene and propylene, ethylene and 1-butene, ethylene and 1-hexene, ethylene and 4-methyl-1-pentene, or ethylene and 1-octene, and more specifically, the olefin copolymer according to one embodiment of the present invention may be a copolymer of ethylene and 1-butene.

[0042] When the olefin-based polymer is a copolymer of ethylene and an alpha-olefin, the amount of the alpha-olefin may be 90% by weight or less, more specifically 70% by weight or less, even more specifically 5% by weight to 60% by weight, and even more specifically 20% by weight to 50% by weight, based on the total weight of the copolymer. When the alpha-olefin is contained in the above range, it is easy to realize the above-mentioned physical properties.

[0043] The olefin polymer according to the present invention having the above physical properties and structural features may be prepared by a continuous solution polymerization reaction in which an olefin monomer is polymerized in a single reactor while feeding hydrogen gas in the presence of a metallocene catalyst composition containing one or more transition metal compounds. Thus, the olefin polymer according to the present invention does not have a block formed by linearly linking two or more repeat units derived from any one of the monomers constituting the polymer. That is, the olefin polymer according to the present invention does not include a block copolymer, and may be selected from the group consisting of a random copolymer, an alternating copolymer, and a graft copolymer, and more specifically, may be a random copolymer.

[0044] In one embodiment of the present invention, the amount of the hydrogen gas fed may be 0.35 to 3 parts by weight, specifically 0.4 to 2 parts by weight, and more specifically 0.45 to 1.5 parts by weight, relative to 1 part by weight of the olefin monomer fed to the reaction system. In one embodiment of the present invention, when the olefin polymer is polymerized by continuous solution polymerization, the hydrogen gas may be fed in an amount of 0.35 to 3 kg / h, specifically 0.4 to 2 kg / h, and more specifically 0.45 to 1.5 kg / h, relative to 1 kg / h of the olefin monomer fed to the reaction system.

[0045] In another embodiment of the present invention, when the olefin polymer is a copolymer of ethylene and alpha-olefin, the hydrogen gas can be fed in an amount of 0.8 to 3 parts by weight, specifically 0.9 to 2.8 parts by weight, more specifically 1 to 2.7 parts by weight, per 1 part by weight of ethylene. In another embodiment of the present invention, when the olefin polymer is a copolymer of ethylene and alpha-olefin and is polymerized by continuous solution polymerization, the hydrogen gas can be fed in an amount of 0.8 to 3 kg / h, specifically 0.9 to 2.8 kg / h, more specifically 1 to 2.7 kg / h, per 1 kg / h of ethylene fed to the reaction system.

[0046] When the polymerization is carried out under the condition that the hydrogen gas is introduced in the amount within the above range, the olefin-based polymer of the present invention can satisfy the above-mentioned physical properties.

[0047] Specifically, the olefin copolymer of the present invention can be obtained by a production method including a step of polymerizing an olefin monomer while introducing hydrogen gas in the presence of a catalyst composition for olefin polymerization comprising a transition metal compound represented by the following chemical formula 1:

[0048] However, in the preparation of an olefin-based polymer according to one embodiment of the present invention, the scope of the structure of the transition metal compound of the following Chemical Formula 1 is not limited to the specific disclosed form, but should be understood to include all modifications, equivalents, or alternatives within the spirit and technical scope of the present invention.

[0049] [ka] In the above Chemical Formula 1, R1 may be the same or different, and each independently represents a metalloid group of a Group 4 metal substituted with hydrogen, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group, a silyl group, an alkylaryl group, an arylalkyl group, or a hydrocarbyl group, and the two R1 may be linked to each other by an alkylidene group containing an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms to form a ring; R2 may be the same or different, and each independently represents hydrogen, halogen, an alkyl group having 1 to 20 carbon atoms, an aryl group, an alkoxy group, an aryloxy group, or an amido group, and two or more of R2 may be bonded to each other to form an aliphatic ring or an aromatic ring; R3 may be the same or different, and each independently represents a nitrogen-containing aliphatic or aromatic ring substituted or unsubstituted with hydrogen, a halogen, an alkyl group having 1 to 20 carbon atoms, or an aryl group, and when there are a plurality of the substituents, two or more of the substituents may be bonded to each other to form an aliphatic or aromatic ring; M is a Group 4 transition metal; Q1 and Q2 each independently represent a halogen; an alkyl group having 1 to 20 carbon atoms; an alkenyl group; an aryl group; an alkylaryl group; an arylalkyl group; an alkylamide group having 1 to 20 carbon atoms; an arylamide group; or an alkylidene group having 1 to 20 carbon atoms.

[0050] In another embodiment of the present invention, in the above-mentioned chemical formula 1, R1 and R2 may be the same or different, and each independently may be hydrogen; alkyl having 1 to 20 carbon atoms; aryl; or silyl; R3 may be the same or different, and may be an alkyl having 1 to 20 carbon atoms; an alkenyl having 2 to 20 carbon atoms; an aryl; an alkylaryl; an arylalkyl; an alkoxy having 1 to 20 carbon atoms; an aryloxy; or an amide, and two or more of R6 may be bonded to each other to form an aliphatic or aromatic ring; Q1 and Q2 may be the same or different and each independently represent halogen; alkyl having 1 to 20 carbon atoms; alkylamide having 1 to 20 carbon atoms; or arylamide. M may be a Group 4 transition metal.

[0051] The transition metal compound represented by the formula 1 is characterized in that the metal sites are connected by a cyclopentadienyl ligand to which tetrahydroquinoline is introduced, and the structural cp-MN angle is narrow, and the Q1-M-Q2 (Q3-M-Q4) angle where the monomers approach is wide. In addition, the cp, tetrahydroquinoline, nitrogen, and metal sites are sequentially connected by a cyclic bond to form a more stable and strong pentagonal ring structure. Therefore, when the compound is activated by reacting it with a cocatalyst such as methylaluminoxane or B(C6F5)3 and then applied to olefin polymerization, it is possible to polymerize an olefin polymer having characteristics such as high activity, high molecular weight, and high space polymerization even at a high polymerization temperature.

[0052] Each of the substituents defined in this specification is described in detail below.

[0053] As used herein, unless otherwise specified, the term "hydrocarbyl group" refers to a monovalent hydrocarbon group having 1 to 20 carbon atoms and consisting only of carbon and hydrogen, regardless of its structure, such as alkyl, aryl, alkenyl, alkynyl, cycloalkyl, alkylaryl, or arylalkyl.

[0054] The term "halogen" as used herein means, unless otherwise indicated, fluorine, chlorine, bromine or iodine.

[0055] The term "alkyl", as used herein, unless otherwise specified, means a straight or branched chain hydrocarbon residue.

[0056] As used herein, unless otherwise indicated, the term "cycloalkyl" refers to cyclic alkyls, including cyclopropyl and the like.

[0057] As used herein, unless otherwise indicated, the term "alkenyl" means either a straight or branched chain alkenyl group.

[0058] The branched chain may be an alkyl having 1 to 20 carbon atoms; an alkenyl having 2 to 20 carbon atoms; an aryl having 6 to 20 carbon atoms; an alkylaryl having 7 to 20 carbon atoms; or an arylalkyl having 7 to 20 carbon atoms.

[0059] The term "aryl" as used herein, unless otherwise specified, refers to an aromatic group having 6 to 20 carbon atoms, and specific examples thereof include phenyl, naphthyl, anthryl, phenanthryl, chrysenyl, pyrenyl, anthracenyl, pyridyl, dimethylanilinyl, and anisolyl, but is not limited to these examples.

[0060] The alkylaryl group refers to an aryl group substituted with an alkyl group.

[0061] The arylalkyl group refers to an alkyl group substituted with an aryl group.

[0062] The ring (or heterocyclic group) means a monovalent aliphatic or aromatic hydrocarbon group having 5 to 20 carbon atoms and containing one or more heteroatoms, and may be a single ring or a condensed ring of two or more rings. The heterocyclic group may or may not be substituted with an alkyl group. Examples of such groups include indoline and tetrahydroquinoline, but the present invention is not limited to these.

[0063] The alkylamino group refers to an amino group substituted with an alkyl group, and examples thereof include, but are not limited to, a dimethylamino group, a diethylamino group, and the like.

[0064] According to one embodiment of the present invention, the aryl group preferably has 6 to 20 carbon atoms, and specific examples thereof include phenyl, naphthyl, anthracenyl, pyridyl, dimethylanilinyl, and anisolyl, but are not limited to these examples.

[0065] In this specification, silyl may be unsubstituted or substituted with alkyl having 1 to 20 carbon atoms, and examples thereof include silyl, trimethylsilyl, triethylsilyl, tripropylsilyl, tributylsilyl, trihexylsilyl, triisopropylsilyl, triisobutylsilyl, triethoxysilyl, triphenylsilyl, tris(trimethylsilyl)silyl, and the like, but are not limited to these.

[0066] The compound of Formula 1 may be, but is not limited to, the following Formula 1-1:

[0067] [ka]

[0068] In addition, compounds having various structures within the range defined in Chemical Formula 1 above may also be used.

[0069] The transition metal compound of formula 1 can introduce a large amount of alpha-olefin as well as low density polyethylene due to the structural characteristics of the catalyst, so that it is possible to produce low density polyolefin copolymers of 0.850g / cc to 0.890g / cc.

[0070] The transition metal compound of Formula 1 can be prepared, for example, by the following method.

[0071] [ka]

[0072] In the reaction formula 1, R1 to R3, M, Q1 and Q2 are as defined in the chemical formula 1.

[0073] The compound of Formula 1 can be prepared by the method described in Korean Patent Publication No. 2007-0003071, the contents of which are incorporated herein in their entirety.

[0074] The transition metal compound of Formula 1 may be used as a polymerization catalyst in the form of a composition further including one or more of the cocatalyst compounds represented by Formulas 2, 3, and 4 below.

[0075] [Chemical formula 2] -[Al(R4)-O] a -

[0076] [Chemical formula 3] A(R4)3

[0077] [Chemical formula 4] [LH] + [W(D)4] - or [L] + [W(D)4] -

[0078] In the above Chemical Formulas 2 to 3, R4 may be the same or different, and each independently is selected from the group consisting of halogen, hydroxyalkyl having 1 to 20 carbon atoms, and hydroxyalkyl having 1 to 20 carbon atoms substituted with halogen; A is aluminum or boron; D's each independently represent an aryl having 6 to 20 carbon atoms or an alkyl having 1 to 20 carbon atoms in which one or more hydrogen atoms may be substituted by a substituent, and in this case, the substituent is at least one selected from the group consisting of a halogen, a hydroxyl having 1 to 20 carbon atoms, an alkoxy having 1 to 20 carbon atoms, and an aryloxy having 6 to 20 carbon atoms; H is a hydrogen atom, L is a neutral or cationic Lewis base; W is a group 13 element; a is an integer of 2 or greater.

[0079] Examples of the compound represented by Chemical Formula 2 include alkylaluminoxanes such as methylaluminoxane (MAO), ethylaluminoxane, isobutylaluminoxane, and butylaluminoxane, and also include modified alkylaluminoxanes in which two or more of the alkylaluminoxanes are mixed together, specifically, methylaluminoxane and modified methylaluminoxane (MMAO).

[0080] Examples of the compound represented by Chemical Formula 3 include trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, dimethylchloroaluminum, triisopropylaluminum, tri-s-butylaluminum, tricyclopentylaluminum, tripentylaluminum, triisopentylaluminum, trihexylaluminum, trioctylaluminum, ethyldimethylaluminum, methyldiethylaluminum, triphenylaluminum, tri-p-tolylaluminum, dimethylaluminum methoxide, dimethylaluminum ethoxide, trimethylboron, triethylboron, triisobutylboron, tripropylboron, tributylboron, and the like. Specifically, the compound may be selected from trimethylaluminum, triethylaluminum, and triisobutylaluminum.

[0081] Examples of the compound represented by the chemical formula 4 include triethylammonium tetraphenyl boron, tributylammonium tetraphenyl boron, trimethylammonium tetraphenyl boron, tripropylammonium tetraphenyl boron, trimethylammonium tetra(p-tolyl) boron, trimethylammonium tetra(o,p-dimethylphenyl) boron, tributylammonium tetra(p-trifluoromethylphenyl) boron, trimethylammonium tetra(p-trifluoromethylphenyl) boron, tributylammonium tetrapentafluorophenyl boron, N,N-diethylanilinium tetraphenyl boron, N,N-diethylanilinium tetrapentafluorophenyl boron, diethylammonium tetrapentafluorophenyl boron, triphenylphosphonium tetraphenyl boron, trimethylphosphonium tetraphenyl boron, dimethylanilinium tetrakis(pentafluorophenyl) borate, triethylammonium tetraphenylaluminum, tributyl Ammonium tetraphenylaluminum, trimethylammonium tetraphenylaluminum, tripropylammonium tetraphenylaluminum, trimethylammonium tetra(p-tolyl)aluminum, tripropylammonium tetra(p-tolyl)aluminum, triethylammonium tetra(o,p-dimethylphenyl)aluminum, tributylammonium tetra(p-trifluoromethylphenyl)aluminum, trimethylammonium tetra(p-trifluoromethylphenyl)aluminum, tributylammonium tetrapentafluorophenylaluminum, N,N-diethylanilinium tetraphenylaluminum, N,N-diethylanilinium tetrapentafluorophenylaluminum, diethylammonium tetrapentafluorophenylaluminum, triphenylphosphonium tetraphenylaluminum, trimethylphosphonium tetraphenylaluminum, tripropylammonium tetra(p-tolyl)boron, triethylammonium tetra(o,p-dimethylphenyl)boron, triphenylcarbonium tetra(p-trifluoromethylphenyl)boron, or triphenylcarbonium tetrapentafluorophenylboron.

[0082] The catalyst composition can be prepared, as a first method, by a method including the steps of: 1) contacting the transition metal compound represented by Chemical Formula 1 with the compound represented by Chemical Formula 2 or Chemical Formula 3 to obtain a mixture; and 2) adding the compound represented by Chemical Formula 4 to the mixture.

[0083] In addition, the catalyst composition can be prepared by a second method in which the transition metal compound represented by the formula 1 is contacted with the compound represented by the formula 4.

[0084] In the first method of the method for producing the catalyst composition, the molar ratio of the transition metal compound represented by the chemical formula 1 and the transition metal compound represented by the chemical formula 2 / the compound represented by the chemical formula 2 or the chemical formula 3 may be 1 / 5,000 to 1 / 2, specifically, 1 / 1,000 to 1 / 10, and more specifically, 1 / 500 to 1 / 20. When the molar ratio of the transition metal compound represented by the chemical formula 1 / the compound represented by the chemical formula 2 or the chemical formula 3 exceeds 1 / 2, there is a problem that the amount of the alkylating agent is very small and the alkylation of the metal compound is not completely performed, and when the molar ratio is less than 1 / 5,000, although the alkylation of the metal compound is performed, there is a problem that the activation of the alkylated metal compound is not completely performed due to a side reaction between the remaining excess alkylating agent and the activating agent which is the compound of the chemical formula 4. In addition, the molar ratio of the transition metal compound represented by the chemical formula 1 / the compound represented by the chemical formula 4 may be 1 / 25 to 1, specifically, 1 / 10 to 1, and more specifically, 1 / 5 to 1. When the molar ratio of the transition metal compound represented by Formula 1 / the compound represented by Formula 4 exceeds 1, the amount of the activator is relatively small, and the activation of the metal compound is not fully achieved, so that the activity of the resulting catalyst composition may be reduced. When the molar ratio is less than 1 / 25, the activation of the metal compound is fully achieved, but the unit price of the catalyst composition may be uneconomical or the purity of the resulting polymer may be reduced due to the remaining excess activator.

[0085] In the second method of preparing the catalyst composition, the molar ratio of the transition metal compound represented by Formula 1 to the compound represented by Formula 4 may be 1 / 10,000 to 1 / 10, specifically 1 / 5,000 to 1 / 100, and more specifically 1 / 3,000 to 1 / 500. If the molar ratio exceeds 1 / 10, the amount of activator is relatively small, and the activation of the metal compound cannot be completed, so that the activity of the catalyst composition produced may be reduced. If the molar ratio is less than 1 / 10,000, the activation of the metal compound is completed, but the remaining excess amount of activator may make the unit price of the catalyst composition uneconomical or reduce the purity of the polymer produced.

[0086] When preparing the catalyst composition, a hydrocarbon solvent such as pentane, hexane, or heptane, or an aromatic solvent such as benzene or toluene may be used as a reaction solvent.

[0087] The catalyst composition may contain the transition metal compound and the cocatalyst compound supported on a carrier.

[0088] The carrier can be any carrier that is used as a carrier in a metallocene catalyst without any particular limitation. Specifically, the carrier can be silica, silica-alumina, silica-magnesia, or the like, and any one or a mixture of two or more of these can be used.

[0089] In particular, when the support is silica, the silica support and the functional group of the metallocene compound of Chemical Formula 1 form a chemical bond, so that almost no catalyst is liberated from the surface during the olefin polymerization process. As a result, it is possible to prevent fouling, which is the entanglement of the reactor wall or polymer particles, during the olefin polymer production process. In addition, the olefin polymer produced in the presence of a catalyst containing the silica support has excellent polymer particle morphology and apparent density.

[0090] More specifically, the support may be silica or silica-alumina that has been dried at a high temperature and contains highly reactive siloxane on the surface thereof by a method such as high-temperature drying.

[0091] The support may further comprise an oxide, carbonate, sulfate or nitrate component, such as Na2O, K2CO3, BaSO4 or Mg(NO3)2.

[0092] The polymerization reaction of the olefin monomer may be carried out by a conventional process applied to the polymerization of olefin monomers, such as continuous solution polymerization, bulk polymerization, suspension polymerization, slurry polymerization, or emulsion polymerization.

[0093] The polymerization reaction of the olefin monomer may be carried out in an inert solvent, and examples of the inert solvent include, but are not limited to, benzene, toluene, xylene, cumene, heptane, cyclohexane, methylcyclohexane, methylcyclopentane, n-hexane, 1-hexene, and 1-octene.

[0094] The polymerization of the olefin polymer may be carried out at a temperature of about 25° C. to about 500° C., specifically, at a temperature of 80° C. to 250° C., more preferably at a temperature of 100° C. to 200° C. The reaction pressure during polymerization is 1 kgf / cm. 2 ~150kgf / cm 2 , preferably 1 kgf / cm 2 ~120kgf / cm 2 , more preferably 5 kgf / cm 2 ~100kgf / cm 2 may be also possible.

[0095] Working Example DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof so that those skilled in the art can easily implement the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the exemplary embodiments set forth herein.

[0096] Catalyst Production Example 1: Production of Transition Metal Compound A [ka] (1) Production of 8-(2,3,4,5-Tetramethyl-1,3-cyclopentadienyl)-1,2,3,4-tetrahydroquinoline (i) Preparation of lithium carbamate 1,2,3,4-Tetrahydroquinoline (13.08g, 98.24mmol) and diethyl ether (150mL) were placed in a Schlenk flask. The Schlenk flask was immersed in a -78℃ low-temperature bath containing dry ice and acetone and stirred for 30 minutes. Then, n-BuLi (39.3mL, 2.5M, 98.24mmol) was added with a syringe under a nitrogen atmosphere to form a pale yellow slurry. Then, the flask was stirred for 2 hours, and the temperature of the flask was raised to room temperature while removing the generated butane gas. The flask was immersed again in a -78℃ low-temperature bath to lower the temperature, and CO2 gas was added. The slurry disappeared due to the introduction of carbon dioxide gas, and a transparent solution was obtained. The flask was connected to a bubbler and the temperature was raised to room temperature while removing carbon dioxide gas. Then, the remaining CO2 gas and solvent were removed under vacuum. The flask was transferred to a dry box, pentane was added, and the mixture was stirred vigorously and filtered to obtain a white solid compound, lithium carbamate, which is coordinated with diethyl ether. The yield was 100%.

[0097] 1 H NMR(C6D6,C5D5N):δ 1.90(t,J=7.2 Hz,6H,ether),1.50(br s,2H,quin-CH2),2.34(br s,2H,quin-CH2),3.25(q,J=7.2 Hz,4H,ether),3.87(br,s,2H,quin-CH2),6.76(br d,J=5.6 Hz,1H,quin-CH)ppm 13 C NMR(C6D6):δ 24.24,28.54,45.37,65.95,121.17,125.34,125.57,142.04,163.09(C=O)ppm

[0098] (ii) Preparation of 8-(2,3,4,5-tetramethyl-1,3-cyclopentadienyl)-1,2,3,4-tetrahydroquinoline [ka] The lithium carbamate compound (8.47g, 42.60mmol) prepared in step (i) was placed in a Schlenk flask. Tetrahydrofuran (4.6g, 63.9mmol) and 45mL of diethyl ether were then added in that order. The Schlenk flask was immersed in a -20℃ low-temperature bath containing acetone and a small amount of dry ice and stirred for 30 minutes, after which t-BuLi (25.1mL, 1.7M, 42.60mmol) was added. At this time, the color of the reaction mixture turned red. Stirring was continued for 6 hours while maintaining the temperature at -20℃. A CeCl3·2LiCl solution (129mL, 0.33M, 42.60mmol) dissolved in tetrahydrofuran and tetramethylcyclopentynone (5.89g, 42.60mmol) were mixed in a syringe and then added to the flask under a nitrogen atmosphere. The temperature of the flask was gradually raised to room temperature, and after 1 hour, the thermostatic bath was removed and the temperature was maintained at room temperature. Then, water (15 mL) was added to the flask, and ethyl acetate was added and filtered to obtain a filtrate. The filtrate was transferred to a separatory funnel, and hydrochloric acid (2N, 80 mL) was added and shaken for 12 minutes. In addition, a saturated aqueous solution of sodium bicarbonate (160 mL) was added to neutralize, and an organic layer was extracted. Anhydrous magnesium sulfate was added to the organic layer to remove moisture, and the organic layer was filtered, and the filtrate was taken and the solvent was removed. The obtained filtrate was purified by column chromatography using a solvent of hexane and ethyl acetate (v / v, 10:1) to obtain a yellow oil. The yield was 40%.

[0099] 1H NMR(C6D6):δ 1.00(br d,3H,Cp-CH3),1.63-1.73(m,2H,quin-CH2),1.80(s,3H,Cp-CH3),1.81(s,3H,Cp-CH3),1.85(s,3H,Cp-CH3),2.64(t,J=6.0 Hz,2H,quin-CH2),2.84-2.90(br,2H,quin-CH2),3.06(br s,1H,Cp-H),3.76(br s,1H,NH),6.77(t,J=7.2 Hz,1H,quin-CH),6.92(d,J=2.4 Hz,1H,quin-CH),6.94(d,J=2.4 Hz,1H,quin-CH)ppm

[0100] (2) [(1,2,3,4-tetrahydroquinolin-8-yl)tetramethylcyclopentadienyl-η 5 Production of [(1,2,3,4-Tetrahydroquinolin-8-yl)tetramethylcyclopentadienyl-eta5,kapa-N]titanium dimethyl [ka]

[0101] (i) [(1,2,3,4-tetrahydroquinolin-8-yl)tetramethylcyclopentadienyl-η 5 Preparation of [,κ-N]dilithium compounds In a dry box, 8-(2,3,4,5-tetramethyl-1,3-cyclopentadienyl)-1,2,3,4-tetrahydroquinoline (8.07 g, 32.0 mmol) prepared in step (1) and 140 mL of diethyl ether were placed in a round-bottom flask, and the temperature was lowered to -30°C, and n-BuLi (17.7 g, 2.5 M, 64.0 mmol) was gradually added while stirring. The temperature was raised to room temperature and the reaction was carried out for 6 hours. After that, the mixture was filtered while being washed several times with diethyl ether to obtain a solid. The remaining solvent was removed by applying a vacuum, and a yellow solid dilithium compound (9.83 g) was obtained. The yield was 95%.

[0102] 1H NMR(C6D6,C5D5N):δ 2.38(br s,2H,quin-CH2),2.53(br s,12H,Cp-CH3),3.48(br s,2H,quin-CH2),4.19(br s,2H,quin-CH2),6.77(t,J=6.8 Hz,2H,quin-CH),7.28(brs,1H,quin-CH),7.75(brs,1H,quin-CH)ppm

[0103] (ii) (1,2,3,4-tetrahydroquinolin-8-yl)tetramethylcyclopentadienyl-η 5 Preparation of dimethyl ,κ-N]titanium In a dry box, TiCl4·DME (4.41 g, 15.76 mmol) and diethyl ether (150 mL) were placed in a round-bottom flask and stirred at -30 °C. MeLi (21.7 mL, 31.52 mmol, 1.4 M) was gradually added. After stirring for 15 minutes, the [(1,2,3,4-tetrahydroquinolin-8-yl)tetramethylcyclopentadienyl-ηη 5 [,κ-N]dilithium compound (5.30g, 15.76mmol) was placed in the flask. The temperature was raised to room temperature and stirred for 3 hours. After the reaction was completed, the solvent was removed by applying a vacuum, the product was dissolved in pentane, filtered, and the filtrate was taken. The pentane was removed by applying a vacuum to obtain a dark brown compound (3.70g). The yield was 71.3%.

[0104] 1 H NMR(C6D6):δ 0.59(s,6H,Ti-CH3),1.66(s,6H,Cp-CH3),1.69(br t,J=6.4 Hz,2H,quin-CH2),2.05(s,6H,Cp-CH3),2.47(t,J=6.0 Hz,2H,quin-CH2),4.53(m,2H,quin-CH2),6.84(t,J=7.2 Hz,1H,quin-CH),6.93(d,J=7.6 Hz,quin-CH),7.01(d,J=6.8 Hz,quin-CH)ppm 13C NMR(C6D6):δ 12.12,23.08,27.30,48.84,51.01,119.70,119.96,120.95,126.99,128.73,131.67,136.21 ppm

[0105] Catalyst Production Example 2: Production of Transition Metal Compound B [ka] (1) Preparation of 2-methyl-7-(2,3,4,5-tetramethyl-1,3-cyclopentadienyl)indoline 2-Methyl-7-(2,3,4,5-tetramethyl-1,3-cyclopentadienyl)indoline was produced in a yield of 19% by the same method as in Production Example 1(1), except that 2-methylindoline was used instead of 1,2,3,4-tetrahydroquinoline in Production Example 1(1).

[0106] 1 H NMR(C6D6):δ 6.97(d,J=7.2Hz,1H,CH),δ 6.78(d,J=8Hz,1H,CH),δ 6.67(t,J=7.4Hz,1H,CH),δ 3.94(m,1H,quinoline-CH),δ 3.51(br s,1H,NH),δ 3.24-3.08(m,2H,quinoline-CH2,Cp-CH),δ 2.65(m,1H,quinoline-CH 2 ),δ 1.89(s,3H,Cp-CH3),δ 1.84(s,3H,Cp-CH3),δ 1.82(s,3H,Cp-CH3),δ 1.13(d,J=6Hz,3H,quinoline-CH3),δ 0.93(3H,Cp-CH3)ppm.

[0107] (2) Preparation of [(2-Methylindolin-7-yl)tetramethylcyclopentadienyl-eta5,kapa-N]titanium dimethyl (i) A dilithium salt compound (compound 4g) coordinated with 0.58 equivalents of diethyl ether was obtained (1.37 g, 50%) in the same manner as in (2)(i) of Production Example 1, except that 2-methyl-7-(2,3,4,5-tetramethyl-1,3-cyclopentadienyl)-indoline (2.25 g, 8.88 mmol) was used instead of 8-(2,3,4,5-tetramethyl-1,3-cyclopentadienyl)-1,2,3,4-tetrahydroquinoline.

[0108] 1 H NMR (Pyridine-d8):δ 7.22(br s,1H,CH),δ 7.18(d,J=6Hz,1H,CH),δ 6.32(t,1H,CH),δ 4.61(brs,1H,CH),δ 3.54(m,1H,CH),δ 3.00(m,1H,CH),δ 2.35-2.12(m,13H,CH,Cp-CH3),δ 1.39(d,indoline-CH3)ppm.

[0109] (ii) Using the dilithium salt compound (compound 4g) (1.37 g, 4.44 mmol) prepared in (i) above, a titanium compound was prepared in the same manner as in (2)(ii) of Preparation Example 1 above.

[0110] 1 H NMR(C6D6):δ 7.01-6.96(m,2H,CH),δ 6.82(t,J=7.4Hz,1H,CH),δ 4.96(m,1H,CH),δ 2.88(m,1H,CH),δ 2.40(m,1H,CH),δ 2.02(s,3H,Cp-CH3),δ 2.01(s,3H,Cp-CH3),δ 1.70(s,3H,Cp-CH3),δ 1.69(s,3H,Cp-CH3),δ 1.65(d,J=6.4Hz,3H,indoline-CH3),δ 0.71(d,J=10Hz,6H,TiMe2-CH3)ppm.

[0111] Example 1 A 1.5L continuous process reactor was filled with hexane solvent (5 kg / h) and 1-butene (0.95 kg / h), and the temperature at the top of the reactor was preheated to 140.7°C. Triisobutylaluminum compound (0.06 mmol / min), transition metal compound B (0.40 μmol / min) obtained in Catalyst Preparation Example 2, and dimethylanilinium tetrakis(pentafluorophenyl)borate cocatalyst (1.20 μmol / min) were simultaneously introduced into the reactor. Then, hydrogen gas (15 cc / min) and ethylene (0.87 kg / h) were introduced into the reactor, and the copolymerization reaction was carried out at 141°C for 30 minutes or more in a continuous process at a pressure of 89 bar to obtain a copolymer. The copolymer was then dried in a vacuum oven for 12 hours or more, and the physical properties were measured.

[0112] Manufacturing Examples 2-5 The copolymerization reaction was carried out in the same manner as in Example Production Example 1, except that the amounts of the transition metal compound, the catalyst and the cocatalyst, the reaction temperature, the amount of hydrogen input, and the amount of the comonomer were changed as shown in Table 1 below, to obtain copolymers.

[0113] Comparative Manufacturing Example 1 DF610 manufactured by Mitsui Chemicals was purchased and used.

[0114] Comparative Manufacturing Examples 2-4 Copolymerization reaction was carried out in the same manner as in Production Example 1, except that the type of transition metal compound, the amount of transition metal compound used, the amount of catalyst and cocatalyst used, as well as the reaction temperature, the amount of hydrogen input, and the amount of comonomer were changed as shown in Table 1 below to obtain copolymers.

[0115] Comparative Manufacturing Example 5 DF710 manufactured by Mitsui Chemicals was purchased and used.

[0116] Comparative Example 6 DF640 manufactured by Mitsui Chemicals was purchased and used.

[0117] Comparative Example 7 EG7447 manufactured by Dow was purchased and used.

[0118] [Table 1]

[0119] Experimental Example 1: Evaluation of physical properties of olefin polymers The physical properties of the copolymers of the above-mentioned Production Examples 1 to 5 and Comparative Production Examples 1 to 4 were evaluated by the following methods, and the results are shown in Tables 2 and 3 below.

[0120] 1) Polymer Density Measured according to ASTM D-792.

[0121] 2) Polymer Melt Index (MI) Measurement was performed according to ASTM D-1238 (condition E, 190°C, 2.16 kg load).

[0122] 3) Weight average molecular weight (Mw, g / mol) and molecular weight distribution (MWD) The number average molecular weight (Mn) and weight average molecular weight (Mw) were measured by gel permeation chromatography (GPC), and the molecular weight distribution was calculated by dividing the weight average molecular weight by the number average molecular weight.

[0123] -Column: PL Olexis -Solvent: TCB (Trichlorobenzene) -Flow rate: 1.0ml / min -Sample concentration: 1.0mg / ml -Injection volume: 200μl -Column temperature: 160°C -Detector: Agilent High Temperature RI detector -Standard: Polystyrene (corrected by a cubic function)

[0124] 4) Polymer melting point (Tm) The melting point was obtained using a differential scanning calorimeter (DSC: Differential Scanning Calorimeter 250) manufactured by TA Instruments. That is, the temperature was raised to 150°C, maintained at that temperature for 1 minute, then lowered to -100°C, and the temperature was raised again to obtain the melting point at the peak of the DSC curve. At this time, the rate of temperature rise and fall was 10°C / min, and the melting point was obtained during the second temperature rise.

[0125] FIG. 1 shows a DSC graph of the polymer of Example Production Example 1, and FIG. 2 shows a DSC graph of the polymer of Comparative Production Example 1.

[0126] 5) High-temperature melting peaks of polymers and T(95), T(90), T(50) The results were obtained by the SSA (Successive self-nucleation / annealing) measurement method using a TA Instruments Differential Scanning Calorimeter (DSC: Differential Scanning Calorimeter 250).

[0127] Specifically, in the first cycle, the temperature was raised to 150° C., maintained at that temperature for 1 minute, and then cooled to -100° C. In the second cycle, the temperature was raised to 120° C., maintained at that temperature for 30 minutes, and then cooled to -100° C. In the third cycle, the temperature was raised to 110° C., maintained at that temperature for 30 minutes, and then cooled to -100° C. In this manner, the process of raising the temperature at 10° C. intervals and cooling to -100° C. was repeated down to -60° C., so that crystallization was carried out for each temperature interval.

[0128] In the final cycle, the heat capacity was determined as the temperature was increased to 150°C.

[0129] The temperature-heat capacity curve thus obtained was integrated for each section, and the heat capacity of each section was fractionated with respect to the total heat capacity. Here, the temperature at which 50% of the whole is melted is defined as T(50), the temperature at which 90% is melted is defined as T(90), and the temperature at which 95% is melted is defined as T(95).

[0130] FIG. 3 shows an SSA graph of the polymer of Example 1, and FIG. 4 shows an SSA graph of the polymer of Comparative Example 1.

[0131] FIG. 5 shows a graph of the fractionated SSA results of the polymer of Example 1, and FIG. 4 shows a graph of the fractionated SSA results of the polymer of Comparative Example 1.

[0132] 6) Hardness (shore A) The hardness was measured according to the ASTM D2240 standard using a TECLOCK GC610 STAND for Durometer and a Mitutoyo Shore hardness tester Type A.

[0133] 7) Tensile and tear strength of polymers The olefin copolymers of Example 1 and Comparative Examples 1 to 3 were each extruded into pellets, and the tensile strength and tear strength at break were measured in accordance with ASTM D638 (50 mm / min).

[0134] [Table 2]

[0135] [Table 3]

[0136] When comparing the olefin polymer of Example 1 and the olefin polymer of Comparative Example 1, which have the same level of density and MI, Fig. 1 and Fig. 2 measured by DSC show similar trends and similar graph forms, and there is not much difference, but Fig. 3 and Fig. 4 measured by SSA show a large difference in the high temperature range of 75 ° C or more. Specifically, a peak is shown at 75 ° C or more in Example 1, whereas the Comparative Examples do not show it. Although Comparative Examples 2 and 3 have peaks in the corresponding range, the size of the peaks is smaller than that of the Example 1. Due to the difference in melting in this high temperature range, Example 1 to 5 can satisfy T(90)-T(50)≦50 and T(95)-T(90)≧10, and it can be seen that they have a wider value of T(95)-T(90) than Comparative Examples 1 to 7.

[0137] Table 3 compares the mechanical strength of Example 1 and Comparative Examples 1, 2, and 3, which have similar levels of density and MI. It can be seen that Example 1 has increased mechanical stiffness due to the introduction of a polymer that melts at high temperatures, and has increased tensile strength and tear strength compared to Comparative Examples 1 to 3.

[0138] Production Examples 1 to 5 are polymers obtained by polymerizing olefin monomers while feeding hydrogen gas, and have a highly crystalline region introduced therein, satisfying T(90)-T(50)≦50 and T(95)-T(90)≧10, and exhibiting high mechanical rigidity. By comparing with Comparative Example 2 and Comparative Example 4, it was confirmed that the mechanical rigidity and the satisfaction of T(90)-T(50)≦50 and T(95)-T(90)≧10 differ depending on whether hydrogen gas is fed during polymerization and the amount of hydrogen gas fed.

[0139] Example 1: Preparation of polypropylene-based composite material 20 parts by weight of the olefin copolymer produced in Example 1 was mixed with 60 parts by weight of a highly crystalline impact copolymer polypropylene (CB5230, manufactured by Daehan Petrochemical Co., Ltd.) having a melt index (230° C., 2.16 kg) of 30 g / 10 min, and talc (KCNAP-400 TM , manufactured by KOCH) (average particle size (D50 20 parts by weight of PO2 (=11.0μm) was added, and 0.1 parts by weight of AO1010 (Irganox 1010, Ciba Specialty Chemicals), 0.1 parts by weight of tris(2,4-di-tert-butylphenyl)phosphite (A0168), and 0.3 parts by weight of calcium stearate (Ca-st) were added as antioxidants, and the mixture was melt-kneaded using a twin-screw extruder to produce a pellet-shaped polypropylene composite compound. At this time, the twin-screw extruder had a diameter of 25Φ, a diameter to length ratio of 40, and was set under the following conditions: barrel temperature 200℃ to 230℃, screw rotation speed 250rpm, and extrusion rate 25kr / hr.

[0140] Examples 2 to 5: Production of polypropylene-based composite materials A polypropylene-based composite material was prepared in the same manner as in Example 1, except that the olefin copolymers shown in Table 4 below were used instead of the olefin copolymer prepared in Example 1. Example 5 differs in the type of polypropylene and the ratio of the olefin copolymer to the polypropylene. The polypropylene shown as CB5290 in Table 4 below is a highly crystalline impact copolymer polypropylene (CB5290, manufactured by Daehan Oil & Chemical Co., Ltd.) with a melt index (230°C, 2.16 kg) of 90 g / 10 min.

[0141] Comparative Examples 1 to 7: Production of polypropylene-based composite materials A polypropylene-based composite material was prepared in the same manner as in Example 1, except that the olefin copolymers shown in Table 4 below were used instead of the olefin copolymer prepared in Example 1. In this case, Comparative Example 7 differs in the type of polypropylene and the ratio of the olefin copolymer to polypropylene.

[0142] The polypropylene shown as CB5290 in Table 4 below is a highly crystalline impact copolymer polypropylene (CB5290, manufactured by Daehan Oil & Chemical Co., Ltd.) having a melt index (230° C., 2.16 kg) of 90 g / 10 min.

[0143] [Table 4]

[0144] Experimental Example 2: Evaluation of the physical properties of polypropylene composite materials In order to confirm the physical properties of the polypropylene composite materials produced in Examples 1 to 5 and Comparative Examples 1 to 7, the polypropylene composite materials were injection molded at a temperature of 230°C using an injection machine to produce test pieces, which were then left in a temperature and humidity controlled room for one day, after which the polymer specific gravity, polymer melt index, tensile strength, flexural strength and flexural modulus, low temperature and room temperature impact strength, and shrinkage were measured. The physical properties of the test pieces produced are shown in Table 5 below.

[0145] 1) Specific gravity Measured according to ASTM D792.

[0146] 2) Polymer Melt Index (MI) The melt index (MI) of the polymer was measured according to ASTM D-1238 (condition E, 230° C., 2.16 kg load).

[0147] 3) Tensile strength and flexural strength Measurements were performed using an INSTRON 3365 instrument according to ASTM D790.

[0148] 4) Low and normal temperature impact strength The tests were conducted in accordance with ASTM D256. The room temperature impact strength was measured at room temperature (23°C), and the low temperature impact strength was measured after leaving the specimen in a low temperature chamber (-30°C) for 12 hours or more.

[0149] [Table 5]

[0150] Referring to Table 5, when comparing polypropylene-based composites containing olefin-based copolymers having similar levels of density and MI value, it can be seen that the polypropylene-based composites of the Examples maintain similar levels of low-temperature impact strength and room-temperature impact strength, and have improved mechanical strength such as tensile strength and flexural strength, compared to the polypropylene-based composites of the Comparative Examples. As a result, it can be seen that the polypropylene-based composites of the Examples contain an olefin-based copolymer that exhibits high mechanical stiffness due to the introduction of a highly crystalline region, thereby increasing the mechanical stiffness of the polypropylene-based composites.

Claims

1. (A) polypropylene; (B) A polypropylene-based composite material containing an olefin-based polymer which is any one of a copolymer of ethylene and 1-butene, a copolymer of ethylene and 1-hexene, a copolymer of ethylene and 4-methyl-1-pentene, and a copolymer of ethylene and 1-octene, which satisfies the following requirements (1) to (3): (1) A melt index (MI, 190°C, 2.16 kg load condition) of 0.1 g / 10 min to 10.0 g / 10 min; (2) the density (d) is 0.860 g / cc to 0.880 g / cc; (3) when measured by differential scanning calorimetry (SSA), T(90)-T(50)≦50 and T(95)-T(90)≧10; Here, T(50), T(90) and T(95) are the temperatures at which 50%, 90% and 95% melt, respectively, when the temperature-heat capacity curve is fractionated in the measurement results by the differential scanning calorimeter precision measurement method (SSA).

2. The polypropylene composite material according to claim 1, wherein the polypropylene (A) has a melt index of 0.5 g / 10 min to 100 g / 10 min measured at 230° C. and a load of 2.16 kg.

3. The polypropylene-based composite material according to claim 1, wherein the polypropylene (A) is an impact copolymer having a melt index of 0.5 g / 10 min to 100 g / 10 min measured at 230° C. and a load of 2.16 kg.

4. The polypropylene composite material according to claim 1, wherein the olefin polymer (B) further satisfies the requirement that the weight average molecular weight (Mw) is 10,000 g / mol to 500,000 g / mol.

5. The polypropylene composite material according to claim 1, wherein the olefin polymer (B) further satisfies the requirement (5) that the molecular weight distribution (MWD) is 1.0 to 6.

0.

6. The polypropylene composite material according to claim 1, wherein the olefin polymer (B) further satisfies the requirement (6) that the melting point is 20°C to 70°C when measured by a differential scanning calorimeter (DSC).

7. The polypropylene composite material according to claim 1, comprising 5% by weight to 40% by weight of the olefin polymer (B).

8. 10. The polypropylene-based composite of claim 1, further comprising an inorganic filler.

9. (A) the inorganic filler is contained in an amount of 0.1 to 40 parts by weight based on 100 parts by weight of polypropylene; The inorganic filler has an average particle size (D 50 9. The polypropylene-based composite material according to claim 8, wherein the average particle diameter is 1 μm to 20 μm.

Citation Information

Patent Citations

  • olefin polymer

    JP2020535267A

  • olefin polymer

    JP2021505711A

  • JPP7416353B

  • Polypropylene based composite

    KR1020190076499A